THE INFLUENCE OF SERVICE QUALITY, STORE ATMOSPHERE, AND CUSTOMER SATISFACTION ON REPURCHASE INTENTION OF FASHION PRODUCTS AT MECCA GALLERY STORE MATANGKULI - Asfiani Rizkina; Halida Bahri; Ikramuddin; M. Subhan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the influence of service quality, store atmosphere, and customer satisfaction on the repurchase intention of fashion products at Mecca Gallery Store Matangkuli. The research method used in this study is a quantitative approach. The instruments in this study include validity and reliability tests, classical assumption tests such as normality, multicollinearity, and heteroscedasticity tests, determination test (R²), and hypothesis testing (t-test). The study was conducted on customers who had previously purchased fashion products at Mecca Gallery Store Matangkuli. The data used in this study is primary data collected through questionnaires distributed to 102 respondents. The data analysis technique employed is multiple linear regression analysis using SPSS 26.0. The results of this study indicate that, partially, the service quality variable does not have a significant effect on repurchase intention, while store atmosphere has a positive and significant effect on repurchase intention, and customer satisfaction also has a positive and significant effect on repurchase intention.